Effect of Foot Reflexology Practice on Acute Pain and Anxiety of Critically ill Patients after Cardiothoracic Surgery - Abdou, Fayza Ahmed; Abd El-Hafez, Amal Ismael (International Journal of Innovative Research in Medical Science, 2018)
Background: One of complementary therapy is foot reflexology practice which is effortlessly, un-costly and with little risks or complications and can be considered as part of nursing procedures for acute pain and anxiety after cardiothoracic surgery. Objective: evaluate the effect of foot reflexology practice on acute pain and anxiety of critically ill patients after cardiothoracic surgery. Research hypothesis: The pain and anxiety score among the interventional group who receiving the foot reflexology practice is lower than that of the control group. Research design: a quasi-experimental research design was used. Setting: This study was conducted in Cardiothoracic and Post-Operative Intensive Care Units at Assuit University Hospital. Subjects: sixty patients were enrolled in this study and assigned equally to intervention and control groups during the period of data collection from February 2015 to February 2016. Results: There were significant differences between the mean of pain and anxiety score of both groups at immediately, and 45 minutes indicating lower mean of pain and anxiety level among intervention group who received foot reflexology practice than control group. Conclusion: The intervention group who received foot reflexology practice had lower pain and anxiety level than the control group who didn’t received foot reflexology practice after cardiothoracic surgery.